Towards a democratic state in Palestine. [...] contributed by the Palestine National Liberation Movement, Fateh, to the 2nd world conference on Palestine held in Amman, Sept. 2-6, 1970 ([General Union of Palestine Students, Kuwaiti Graduate Society, 1971)
2nd international symposium on Palestine. Kuwait 13-17 February 1971.